Validation of a method for cylindrospermopsin determination in vegetables: Application to real samples such as lettuce (lactuca sativa l.) - Prieto A.I. (2018)
Reports on the occurrence of the cyanobacterial toxin cylindrospermopsin (CYN) have increased worldwide because of CYN toxic effects in humans and animals. If contaminated waters are used for plant irrigation, these could represent a possible CYN exposure route for humans. For the first time, a method employing solid phase extraction and quantification by ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) of CYN was optimized in vegetables matrices such as lettuce (Lactuca sativa). The validated method showed a linear range, from 5 to 500 ng CYN g−1 of fresh weight (f.w.), and detection and quantitation limits (LOD and LOQ) of 0.22 and 0.42 ng CYN g−1 f.w., respectively. The mean recoveries ranged between 85 and 104%, and the intermediate precision from 12.7 to 14.7%. The method showed to be robust for the three different variables tested. Moreover, it was successfully applied to quantify CYN in edible lettuce leaves exposed to CYN-contaminated water (10 µg L−1), showing that the tolerable daily intake (TDI) in the case of CYN could be exceeded in elderly high consumers. The validated method showed good results in terms of sensitivity, precision, accuracy, and robustness for CYN determination in leaf vegetables such as lettuce. More studies are needed in order to prevent the risks associated with the consumption of CYN-contaminated vegetables. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.